(untitled) (Lex Scientia Law Review, 2024)
The rapid growth of digital technology has profoundly impacted both human lives and the environment. According to the 2024 Digital Economy Report: Shaping an Environmentally Sustainable and Inclusive Digital Future, India’s global share of screens, computers, and small IT and telecommunication (SCSIT) waste has increased from 3.1% in 2010 to 6.4% in 2022. The United Nations Conference on Trade and Development (UNCTAD) also reported a 163% increase in India’s generation of electronic waste from SCSIT. E-waste, due to the presence of hazardous materials like heavy metals, lead, and mercury, poses significant environmental and health risks, necessitating proper disposal methods. A key challenge is the growing reliance on digital technologies for essential services, such as e-commerce and e-banking. The expansion of human rights to include digital rights has created a conflict between the freedom of expression and the duty to protect the environment, especially regarding climate change. This article explores the extent of dependency on electronic devices, purchasing patterns, and attitudes toward responsible e-waste disposal and recycling. It examines the effectiveness of India’s current legal and policy framework for e-waste management, focusing on the informal sector’s recycling practices, which pose additional risks. Using empirical data collected from working professionals, students, and homemakers, the study finds that while electronic device ownership is widespread, with most respondents owning more than five devices, e-waste disposal practices are largely irresponsible. Discarded devices are often stored rather than recycled or sold to authorized collectors. This indicates a lack of awareness, resources, and proper infrastructure. The findings underscore the need for a comprehensive policy framework that mandates responsible usage and disposal, empowers municipalities with necessary resources, and penalizes illegal recycling practices.